The Influence of Company Size, Profitability and Leverage on Corporate Social Responsibility of Corporate Platinum Award Recipient - Hilya Syilfania; Parawiyati Parawiyati; Listyowati Listyowati (University of Merdeka Malang, 2022)
This study aims to examine the effect of Firm Size (Size), Profitability (ROA), and Leverage (DAR) on the disclosure of Corporate Social Responsibility (CSR) of companies that receive platinum awards in 2021. The period used in this study are listed companies. as the recipient of the 2021 platinum award which was listed on the Indonesia Stock Exchange during 2016-2020. This research is an associative causality study using a quantitative approach. The sample in this study as many as 7 companies that received the platinum award in 2021 were determined based on the purpose sampling method. Data is collected through documentation by taking secondary data. The data analysis technique used is multiple linear regression. The results of this study indicate that the size of the company (Size) has a positive and significant effect on CSR disclosure, Profitability has no effect on CSR disclosure, and Leverage has a negative and significant effect on CSR disclosure. This means that the effect of firm size as measured by assets and leverage as proxied by DAR (Debt Assets Ratio) has an influence on CSR disclosure. However, for companies with high profits and obtaining platinum awards listed on the Exchange during the observation, profitability has no effect on CSR disclosure.